TLR2 on blood monocytes senses dengue virus infection and its expression correlates with disease pathogenesis - José A. Aguilar-Briseño (Nature Portfolio, 2020)
The mechanisms underlying immunpathologies in dengue virus (DENV) infection are incompletely understood. Here, authors show that TLR2 recognizes DENV particles inducing cytokine expression and activating vascular endothelium cells in vitro, and that TLR2 expression on monocytes correlates with disease severity in patients.